Relativistic effects in BDS-3 high-accuracy intersatellite time synchronization. Issue 10 (15th May 2023) - Yang, Jianhua; Hu, Xiaogong; Zhou, Wei; Zhou, Sanshi; Tang, Chengpan; Song, Yezhi; Liu, Li; Yang, Yufei; Tian, Qiuning; Liu, Jinhuo; Liu, Yuchen; Xing, Nan; et al.
Abstract: The Global Navigation Satellite Systems (GNSSs) apply conventional relativistic corrections to correct apparent clock offsets. However, with the continuous improvements made to time synchronization approaches and onboard atomic clocks, this model has obviously limits the accuracy improvements of BDS-3 intersatellite time synchronization, and also limited the apparent performance of BDS-3 onboard atomic clocks. This study demonstrates that the amplitude of GNSS conventional relativistic periodic errors can reach 0.08 ns for BDS-3 MEO and IGSO satellites within a day, and 0.40 ns within a month. The frequency stability of the errors' signal can reach 1.33E-14 (approximately10000 s) and 1.78E-15 (approximately1 day), and the absolute influences on the predicted clock offset accuracy can reach 0.05 ns (1 h), 1.08 ns (1 day). Notably, the above signals caused by the model errors are found in the results of current high-accuracy intersatellite time synchronization based on BDS-3 intersatellite links (ISLs). After adopting a higher-accuracy relativistic correction model, the frequency instability of BDS-3 intersatellite clock offsets is obviously reduced, and the RMS of 24 h fitting residual can be reduced by approximately 60% from 0.12 ns to 0.05 ns. The average 2 h 95% predicted error decreases by approximately 17% from 0.38 ns to 0.32 ns. These results indicate that this high-accuracy relativistic correction model can improve both the BDS-3 satellites' time synchronization accuracy and the BDS-3 apparent clock offset prediction capability. This study, thus contributes to time synchronization research and signal-in-space accuracy improvements for BDS-3.